Pelatihan Public Speaking sebagai Sarana Pengembangan Wirausaha Muda Kader PMII Kota Bekasi: Public Speaking Training as a Means of Developing Young Entrepreneurs among PMII Cadres in Bekasi City - Noviarini, Tiara; Waluyo, Puji; Maslihan, Maslihan; Aviantono, Bambang; Lestari, Hardita Amalia Sriayu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Public speaking is vital for young entrepreneurs to express ideas confidently and clearly. However, many students lack this ability due to limited access to practical training. This program aimed to improve the communication skills of student organization members through practice-based public speaking training. The two-day training was held at the Nahdlatul Ulama Hall in Bekasi City and involved 30 Indonesian Islamic Student Movement participants. The method included lectures, discussions, and business presentation simulations. Evaluation results significantly improved confidence, message structure, and vocal techniques. Participants also expressed greater interest in developing their business ideas. The activity demonstrated that contextual and hands-on training effectively enhances students' communication skills. This program has strong potential to be replicated as a model for empowering youth organizations in developing community-based young entrepreneurs.